Songketchain: A Framework to Protect Unique Cultural Product using Blockchain Technology - Muhammad Hassif Imran, Muhammad Harris Irwan; Johari, Abdullah; Adnan, Shahid Khan (2022)
Songket market in Sarawak has been established since 1970, making it one of the longest existing cultural and handmade products. Songket preservation is essential to ensure the originality of the artwork in the community. An effort can be done by encouraging the community to report pirated pattern. However, the method available does not lessen the case of pirated pattern in the songket market. Songket in Sarawak are mainly copied by parties that want to make profit from creating copycat product of lesser quality and value but being sold as original merchandise. By creating a new system that can detect the ownership of the songket pattern, it will increase the value of the songket pattern. The proposed system is to assist the creator of the songket to preserve their songket pattern. The main objective of the project is to preserve the authenticity of the produced songket. This is achieved through the introduction of a framework for traceability and traceability of songket product and production process, by utilizing a blockchain solution. A generic framework has been proposed which will be implemented in the next stage of this research.